Republic of Lithuania : 2022 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2022)
The strong post-pandemic economic recovery was leading to an overheating economy and demand-side inflationary pressures. The war in Ukraine, including its impact on commodity prices, has, however, negatively impacted economic activity and further intensified inflationary pressures. With higher inflation for longer, policies should aim at preserving stability over the near-term while supporting the economy adapt to a higher interest rate environment over the medium-term. Although the current sociopolitical situation is less conducive to structural reforms, these remain key to ensuring sustained productivity growth that will support high wage growth and faster income convergence with Western Europe.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Lithuania, Republic of